Sexual harassment a reference handbook - Smith, Merril D. 1956- (California Bloomsburry Publishing, Inc., 2024)
Providing an indispensable resource for high school and college readers investigating sexual harassment in the United States, Sexual Harassment: A Reference Handbook is a comprehensive summary of history, current events, possible solutions, and resources
Background and history-- Problems, controversies, and solutions-- Perspectives-- Profiles-- Data and documents-- Resources-- Chronology
Includes bibliographical references and index.
Keywords: Sexual harassment; Sexual harassment of women